Seed bank in an oak forest of Quercus delgadoana in the central zone of the Sierra Madre Oriental, Mexico - Calva-Soto, Karina; Pavón, Numa P.; Ramírez-Marcial, Neptalí (Instituto de Ecología, A.C., 2022)
Background and Aims: Oak forests have been considered climax communities with high structural variation and biodiversity. However, few studies have been surveyed about seed banks as a germplasm source that may help understanding of ecological succession and the natural recovery of that ecosystem. Therefore, this work’s objective was to carry out an inventory of species in the seed bank of an oak forest dominated by Quercus delgadoana located in the central zone of the Sierra Madre Oriental, Mexico.Methods: Soil samples were collected into four circular parcels of 400 m2. Seed content in every soil sample was manually extracted. Posteriorly, the soil was put into a greenhouse for five months to seed germination and obtain seedlings. Then, seeds and seedlings were determined and classified according to their successional affinities, life form, and dispersion modes.Key results: Two thousand seeds corresponding to 20 families, 40 genera, and 48 species were obtained. The most abundant family was Asteraceae with 20 species. Simsia amplexicaulis was the most abundant species. The seeds of pioneer and intermediate successional species were the most representative with 85%, of the total. Zoochory (50%) was the main means of seed dispersal.Conclusions: The composition of the seed bank was not related to the standing vegetation. Only 15% of the seeds were from trees. The short sampling period did not allow for analyzing the seed bank dynamics, transitory or permanent. However, the seed bank composition constituted by species of initial, secondary, and late successional stages has the potential to regenerate the standing vegetation through ecological succession.